Pelatihan Self-Control For Pupils (Stop) untuk Meningkatkan Kontrol diri Siswa SMP - Yudhistira Adi Perdana; Diana Setiyawati (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2018)
Teenagers are a transition to adulthood. At that time, adolescents experienced various changes in his life. Teenagers are at risk of experiencing various problems. Characteristics of these teenagers make it requires a skill in coping with the problem. Self-control is one of the most important factors in adolescent life. Self-control has two main components, namely emotion expression and adaptive behavior. Self-control can be improved with training. This study aims to determine the effect of Self-control for Pupils (STOP) training on self-control of Junior High School. Student self-control is measured using self-control scale. The subjects in this study were eight people of Junior High School who became experimental groups. The results of the study indicate that Self-control for Pupils (STOP) training does not significantly affect student self-control (t = -1,158; p = 0,285; p > 0.05).